Investigation of the Effect of Steel Plate Size and Elevated Temperature on Critical Load in Stability Tests (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper presents the results of a study of the effect of epoxy-polyester-based powder coatings on the critical strength of plate samples made of rolled sheet steel. The results obtained show that the model using flat elements gives a more accurate result than the model using three-dimensional elements. The best agreement with the experiment was shown by the results obtained in Ansys using the Eigenvalue bucling function, less than 1%. The worst agreement with the experiment was shown by the results obtained in Ansys using Solid elements, about 70%.